ELECTROCHEMICAL OXIDATION OF NITROGEN (II) OXIDE IN THE NEUTRAL MEDIUM - Baeshov Abduali Baeshovich; Aibolova Gulnar Kurbantayevna; Tuleshova Elmira Zhanbirbayevna; Ozler Mehmet Ali (Scientific Journal of Pedagogy and Economics, 2019)
Electrochemical oxidation of nitrogen oxide was considered in the work. The study was carried out in the sodium sulphate solution. The effects of current density in the anode, electrolyte concentration, granular electrode layer thickness and volume of dispersed gas on the oxidation rate of nitrogen (II) oxide and the current output of its oxidation were investigated. The experiments were carried out in a thermostated electrolysis cell in galvanostatic conditions. A granular graphite electrode was used as anode and graphite plate as a cathode, the duration of the experiments was 0.5 hours. Nitrogen (II) oxide gas was supplied at a certain speed at the bottom of the electrolysis cell. The study discovered that nitrate ions were formed as the main product. Optimal parameters of the electrochemical oxidation of nitrogen oxide were determined.